Moda como expressão de identidade no mundo contemporâneo - Moura, Larissa Leal (2018)
Fashion emerged in the West in the Renaissance, where it played the role of social distinction, since the clothes were not accessible to all classes and, consequently, by the way it was dressed, it was possible to identify which social layer that subject belonged to. According to Lipovetsky (2009), what defines the fashion system is the conjunction of the logics of the ephemeral and aesthetic fantasy, which only found space in modern societies. Anthony Giddens (1991) asserts that the modern era differs from others, especially because of its high dynamism, such a rapid pace of social change has never been seen in other times as it does in modernity. In addition, the breadth and depth of social change is much greater, affecting social practices and modes of behavior, so-called "late modernity" is the present moment, the most marked phase of its characteristics. In Psychology, fashion plays a significant role in identity, acting between the individual and society, because through clothing it is possible to express and communicate and, in many cases, it functions as a symbol of belonging. When we think of fashion as an expression of identity in the contemporary world, the notion of identity adopted was that of the postmodern subject of Stuart Hall (2006), who considers it fragmented, multiple, contradictory, breaking with the vision of identity of traditional societies. In the light of this, a bibliographical review of articles on this topic in Psychology in Portuguese, in the last ten years (2007-2017), on the SciELO website (Scientific Electronic Library Online) and on the electronic journals of the PePSIC, with the objective of ascertaining what has been produced on this subject. In the subsequent stage, an exploratory study was conducted through a focus group with six young people aged 19 to 24, conducted twice, in order to investigate the relationship between fashion and identity, as this appears in their discourse about the way they dress. The data were elaborated through Bardin's (2016) content analysis, defined by Moraes (1999) as "a research methodology used to describe and interpret the content of every class of documents and texts." Based on the theoretical foundation, the categories were created social positioning, self-expression, values/ideals and gender and sexuality, articulating the results to the central reflection on fashion and identity in the contemporary world. It was noticed that the notion of identity is not limited only to the clothing, but to the own speech presented by the members of the group, who made use of specific terms of the fashion area, establishing a kind of connection between such members, despite the identified identity distinctions for themselves. Because it is a focal group carried out with young people with some previous knowledge about fashion, it was possible to perceive, also, reflections on the use of fashion in an ambivalent relationship, characterized by the search for belonging in specific groups and by the differentiation of the subject, as a form of to position itself politically and socially. In the discussion, transferential and countertransferential aspects were presented, from the choice of study object, to the composition of the group and even in relation to the procedure and progress of the research, as well as my participation as a researcher.